The dark side of the game : my life in the NFL - Green, Tim, 1963- (New York, NY : Warner Books, 1996)
The author, a former defensive end for the Atlanta Falcons, presents an inside look at the National Football League, reporting on the good and bad things that go on away from the prying eyes of the public and the media.
Includes index.
Keywords: National Football League; Football -- Social aspects -- United States